INTEGRASI SOSIAL DALAM AKTIVITAS PEMENUHAN KEBUTUHAN EKONOMI PENDUDUK TRANSMIGRASI DAN PENDUDUK ASLI DI DESA KOROBONDE KECAMATAN LEMBO KABUPATEN MOROWALI UTARA - Laempu, Visca Evrita; Kawung, Evelin J. R.; Tasik, Femmy C. M. (HOLISTIK, Journal Of Social and Culture, 2020)
The problem of population density, development speed, uneven spread, relatively low average productivity, unemployment and the problem of the workforce, has long been the center of attention and is part of the improvement target in Indonesia's development strategy. One such development program is through transmigration. Population density in the island of Java Madura, Bali and Lombok, compared to the distance from other islands in Indonesia, the population inequality is very large. Therefore, the population equality is continuously encouraged one of them with the transmigration program.The implementation integrates various related programs in both economic, social and cultural areas. With such an idea, the development of Transmigration has a feature of social development introduced, especially in integrating economic development with social development to realize social welfare.Korobonde Village is one of the transmigration villages located in Lembo sub-district, Morowali Utara Regency, Sulawesi Tengah Province, the transmigrants who came to Korobonde village are those of the Jawa Tengah, and the Jawa Timur.With the connectivity and cultural dependence of migrant citizen and local residents, especially in the field of percentage, social life is happening in every day, social fieldomi is a major factor in the process of social integration, cooperation between local ethnicity and migrant citizen is a mixture of several ethnic groups that exist in Korobonde village.Â Keywords: integration, fulfillment needs, transmigration